Understanding immersion in zinc fixed-point cells using factorial design of experiments. (21st December 2020) - da Silva, Rodrigo; Pearce, Jonathan
Abstract: The objective of this study was to investigate the 'lift-off effect' in zinc open cells, where an anomalously large change in temperature is observed when the standard platinum resistance thermometer (SPRT) is lifted off the bottom of the re-entrant tube during an immersion profile measurement. The goal was to determine the most important influences and hence what measures could be taken to mitigate it. The influences investigated were the filling gas, re-entrant tube material, re-entrant tube exterior surface condition, and the SPRT design. For each of these influence variables, three options were chosen. Since testing all combinations of different configurations arising would be extremely time consuming, the authors employed the optimal 'design of experiments' method using orthogonal arrays described by the Taguchi method, which is commonly used in manufacturing to optimise processes. Nine test configurations were identified, giving the necessary information on the interrelation between all influence variables. According to these results, the ideal configuration that yields the optimum immersion profile is a borosilicate tube, with full sandblasting and using nitrogen as filling gas for the cell. In addition, one particular SPRT design was found to be the least sensitive to the lift-off effect.